Natural genetic variation quantitatively regulates heart rate and dimension - Gierten, Jakob; Welz, Bettina; Fitzgerald, Tomas; Thumberger, Thomas; Hummel, Oliver; Leger, Adrien; Weber, Philipp; Hassel, David; Hübner, Norbert; Birney, Ewan; Wittbrodt, Joachim (bioRxiv beta, 2023)
The polygenic contribution to heart development and function along the health-disease continuum remains unresolved. To gain insight into the genetic basis of quantitative cardiac phenotypes, we utilize highly inbred Japanese rice fish models, Oryzias latipes, and Oryzias sakaizumii. Employing automated quantification of embryonic heart rates as core metric, we profiled phenotype variability across five inbred strains. We observed maximal phenotypic contrast between individuals of the HO5 and the HdrR strain. HO5 showed elevated heart rates associated with embryonic ventricular hypoplasia and impaired adult cardiac function. This contrast served as the basis for genome-wide mapping. In a segregation population of 1192 HO5 x HdrR F2 embryos, we mapped 59 loci (173 genes) associated with heart rate. Experimental validation of the top 12 candidate genes in loss-of-function models revealed their causal and distinct impact on heart rate, development, ventricle size, and arrhythmia. Our study uncovers new diagnostic and therapeutic targets for developmental and electrophysiological cardiac diseases and provides a novel scalable approach to investigate the intricate genetic architecture of the vertebrate heart. - One-Sentence Summary Key loci for vertebrate heart function mapped and validated, highlighting diagnostic and potential therapeutic targets for cardiac disorders.
Gesehen am 15.02.2024